Don't sweat it, hire it : an A to Z guide to finding, hiring & managing home improvement pros - Schmidt, Philip (Creative Pub. International, 2007)
"Easy-to-understand guide to hiring professionals to do your home repairs and improvements"--Provided by publisher.